Assessing average annual air temperature trends using the Mann–Kendall test in Kosovo - Milivoj B. Gavrilov; Slobodan B. Marković; Natalija Janc; Milena Nikolić; Aleksandar Valjarević; Blaž Komac; Matija Zorn; Milan Punišić; Nikola Bačević (Acta Geographica Slovenica, 2018)
The annual trends of surface mean monthly air temperature and monthly extreme temperatures were analyzed from ten meteorological stations in Kosovo. The data refer to observation periods between 1949 and 1999 for four stations, and observation periods between 1965 and 1999 for the remaining six stations. Trends were analyzed for nine time series. Positive trends were found in six series, and negative trends were found in three series. After an assessment of these trends using the Mann–Kendall test, positive trends were confirmed in four series, a negative trend was confirmed in one series, and in one series there was no trend, whereas trends were characterized as slightly positive in two time series and slightly negative in one series.